Phylogeny of Middle–Late Ordovician lituitid cephalopods based on cladistic analysis. (3rd May 2021) - Fang, Xiang; Pohle, Alexander; Kröger, Björn; Aubrechtová, Martina; Burrett, Clive; Zhang, Yunbai; Zhang, Yuandong
Abstract : Phylogenetic studies are rare in early Palaeozoic cephalopods. Here, we present the first cladistic analysis of the order Lituitida based on published, as well as some new, material. Three clades are recovered within the ingroup of lituitids, Sinoceras, Ancistroceras and Lituites ; the former two groups correspond to the family Sinoceratidae, and the latter one to the Lituitidae. The topology shows that the Sinoceratidae represents the basal branch, while the Lituitidae represents a monophyletic, derived clade. Furthermore, we describe new material of four species (three of which are newly defined) in four genera of the order Lituitida from the well-exposed, Middle to Upper Ordovician of Hubei (South China). The described species include Lituites evolutus Fang, Chen & Zhang, Sinoceras complexum Fang sp. nov., Tyrioceras longicameratum Fang sp. nov. and Rhynchorthoceras yizanense Fang sp. nov. Tyrioceras longicameratum from South China is the first reported occurrence of Tyrioceras in China, which has significant palaeogeographical implications. http://zoobank.org/urn:lsid:zoobank.org:pub:470C958E-26DD-4A2E-B0FC-4B2B178367FE